Upaya Meningkatkan Rasa Percaya Diri Anak Usia 5-6 Tahun Melalui Kegiatan Bermain Ular Tangga Raksasa di Kober Minhajul Karomah - Titin Supriatin; Redi Awal Maulana; Elnawati Elnawati (PT. Alahyan Publisher Sukabumi, 2025)
This research aims to increase the confidence of children aged 5-6 years through the activity of playing giant snakes and ladders in Kober Minhajul Karomah. Self-confidence is an important aspect of children's social-emotional development that needs to be stimulated from an early age so that children are able to express their opinions, dare to try new things, and believe in their own abilities. The research method used is Class Action Research (PTK) which is carried out in two cycles. Each cycle consists of stages of planning, implementation of actions, observation, and reflection. The subjects of this study are 15 children of group B. Data collection techniques use observation, documentation, and field notes. The results of the study showed an increase in children's confidence from pre-action to cycle I and from cycle I to cycle II. This increase can be seen from the indicators of children's courage in speaking their minds, appearing in front of friends, and completing tasks with confidence when playing giant snake and ladder. Based on these results, it can be concluded that the giant snake and ladder play activity is effective in increasing the confidence of children aged 5-6 years in Kober Minhajul Karomah.